Pembelaan Terpaksa Melampaui Batas (Noodweer Excess) Dalam Konsep Reposisi Korban - Puspanegara, I Gusti Ngurah Dwi; Wulandari, Ni Gusti Agung Ayu Mas Tri; Luh Putu Yeyen Karista Putri (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
The victim who is in the position of being the perpetrator of defense exceed the limit due to the act of murder committed against the perpetrator of begal in criminal law regulated in Article 49 Paragraph (2), which is known as Noodweer Exces. This study aims to identify situations where defense exceed the limit in the context of the victim's role reversal in the case of the crime of robbery. The study applied normative legal research as the method. The approach involves analyzing and describing legal materials such as relevant literature, journals, and regulations, focusing on interrelated primary and secondary legal sources. The main difference with previous study is the emphasis on statutory analysis and case approach, as well as the application of the theory of criminal elimination, the theory of negative proof, and the principle of culpa in causa as supporting theoretical foundations. The findings show that, in principle, criminal regulations in Indonesia protect from a legal perspective against acts of defense carried out by individuals, in this case involved as victims of a criminal offense. Therefore, acts of defense exceed the limits are considered not criminalizable because defense is a right owned by everyone to fight against actions contrary to legal provisions. A person is considered in forced defense if they meet the conditions stipulated in Article 49 Paragraph (2) of the criminal law. These conditions include the act of defense that exceeds the established limits, the direct effect of severe mental or mental shock due to the attack that occurred at that time, and the act of defense in response to the attack or threat of attack. However, the granting abolition of punishment also depends on the results of the trial evidence in this case, which determines whether the perpetrator entitled to obtain it or not.